FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PRODUKSI JAGUNG DI DESA KARYAMUKTI KECAMATAN MOOTILANGO KABUPATEN GORONTALO - Lagarusu, Herti; Machmud, Joice; Paramata, Sri Hantuti; Imbran, Harijono (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2025)
This study aims to determine and analyze whether: 1) area (X1), labor (X2) and capital (X3) have a partial and significant effect on corn production, and whether 1) area (X1), labor (X2) and capital (X3) have a simultaneous and significant effect on corn production in Karyamukti Village, Mootilango District. The research method used is research with a quantitative approach and descriptive type. The results of the study are: The results of corn production by farmers in Karyamukti Village, Mootilango District, Gorontalo Regency are 99.20 percent influenced by land area factors (X1), labor factor (X2), and capital factor (X3). Based on the equation Y = 10.369 + 0.688X1 + 2.128X2 + 1.523X3, it shows a very large possibility for farmers to increase their production by increasing the use of land area factors, labor factor, and capital factor for their corn planting business production. Partially, all factors studied, namely land area factors (X1), labor factors (X2), and capital factors (X.) Capital factors (X3) have a positive and significant effect on the amount of corn production produced by farmers in Karyamukti Village, Mootilango District, Gorontalo Regency. Simultaneously, land area factors (X1), labor factors (X2), and capital factors (X3) have a positive and significant effect on the amount of corn production produced by farmers in Karyamukti Village, Mootilango District, Gorontalo Regency